Topos of Kazan in Russian Poetry of the Late XX — Early XXI Centuries: Features of Functioning and Poetics - V. R. Amineva (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The article deals with the issue related to the peculiarities of the functioning of the “Kazan text” in the works of R. Kutui, R. Bukharaev, E. Blinova and L. Gazizova. The relevance of the study is due to the growing interest of scientists in such types of discourse as supertext. The author proceeds from the fact that the poetics of artistic space is associated with the types of subjective-figurative structures that are formed in the poetry of poets. The novelty of the research is seen in the fact that the types of dialogical relations between lyrical subjects and the city are highlighted. It is shown that Kazan in the works of poets embodies the transpersonal and external in relation  to the main lyrical situation and its heroes. It is concluded that in the poetry of R. Kutui, a multifaceted image of the city is created, with which the lyrical hero establishes relations of unity and interpenetration. It is emphasized that in the works of R. Bukharaev, the attitude to his hometown is ambivalent and reflects the “fluidity”, the  variability of the “I” position. The results of a comparative analysis of the lyrics of E. Blinova and L. Gazizova are presented: Kazan in the works of E. Blinova is a generalized-typical image that objectifies the stages of the heroine’s biography; the urban world of L. Gazizova is extremely concrete and comprehended as an individual-personal space of life.